Annulus criteria for oscillation of nonlinear second order elliptic equations - Xu, Zhiting (Utilitas Mathematica, 2013)
Annulus oscillation criteria are established for a nonlinear second order elliptic equation by utilizing the partial Riccati technique and the Leighton's variational principle. In contrast to the existing results in the literature, for the special cases when N = 1, our results unify, extend and include the recent oscillation criteria for some forced second order ordinary differential equations due to Nasr, Wang, Wong, Yang, and when N ≥ 2, those results also extend and improve the main results of Zhuang for certain second order superlinear elliptic equations.